EVOLVING ROLE OF CAR T-CELL IN CANCER IMMUNOTHERAPY - SULAIMAN, AMAL A.; Al-SHAMAA, ZAINAB AMER; Al-ASSADI, MOHAMMAD EMAD (International Journal of Current Pharmaceutical Research, 2019)
Safety profiles of newly developed anti-cancer therapies is the main goal for efficient treatments to improve survival rates. Therefore, continuous efforts carried out to develop a therapeutic strategy with better outcomes. The concept of immune-oncology, which utilizes and enhances the capacity of human immune system was developed as an eventual opportunity to enhance remissions and limit the relaps of the disease. Later progression of cellular immunetherapies involve the introduction of genetically engineered T cells having chimeric antigen receptors (CARs) that embraced an antibody-derived antigen recognition domain connected to an internal T-cell signaling domain, so can recognize their targets with high degree of tumor selectivity. This approach showed vigorous antitumor outcomes and full recovery in end-stage patients suffering from liquid cancers as leukemia and lymphoma. However, still there is a challenge for bringing genetically modified T-cell immunotherapy to many patients with different tumor types including solid tumor. On other hand, studies indicated the potential to broaden T-cell–based therapies and foster for other possible applications beyond oncology as organ transplantation and autoimmunity. Therefore, this review aimed to illustrate the clinical applications, challenges, and approaches for more efficient clinical employment of CAR T cell therapies.